Diviziunea digitală. Accesul și utilizarea internetului în România, comparativ cu țările Uniunii Europene - Tufă, Laura (Calitatea Vieții, 2010)
This paper brings to attention the concept of digital divide and social inequalities of the uses of internet at an European and at a local level, through the outlining of some theoretical perspectives concerning the social effects of the internet. Also, this article shortly analyses, through a comparative perspective, the European differences concerning the evolution of e-inclusion stages, at different moments and between differently developed countries. At an individual level, we find Romania in the group of low acces and uses of the internet, with a internet-user profile that reinforces the already existing inequalities between social categories, when taking into account age, level of education and occupational status. Moreover, the growth of internet using is higher at those social categories which already have high digital abilities, this fact indicating the potentially deepening of those inequalities, if the intervention is lacking.